PERANAN PROFESIONALISME KINERJA PEGAWAI DALAM PELAYANAN PUBLIK DI KELURAHAN DADI MULYA KOTA SAMARINDA - Nirwana, Nirwana (PREDIKSI, 2016)
The purpose of this study to assess the role of professionalism performance of employees in the public service in the village of Dadi Mulya Samarinda. Analysis of the data used in this study is a parametric statistical correlations, namely the product moment correlation coefficient and simple linear regression analysis with a total population of 20 respondents. Based on the correlation between the performance of employees with professionalism role of public service proved to have a strong relationship and a positive value. This can be proved by using product moment analysis is r = 0.619214 guidelines to provide interpretation dikemukaan by Riduwan (2010: 62) is in the interval 0.60 to 0.799 are included in the category level as well as significant a strong relationship to the quality of public services , This means that if the role of the professionalism of the performance of employees increases, the quality of public services generated will also increase.